Blood levels of antioxidants during age-related macular degeneration treatment by rheohaemapheresis - Aufartova, Jana; Blaha, Milan; Kasalova, Eva; Honegrova, Barbora; Cervinkova, Barbora; Kujovska Krcmova, Lenka; Plisek, Jiri; Lanska, Miriam; Sobotka, Lubos; Solichova, Dagmar (Biomedical papers, 2015)
Aims: Rheohaemapheresis treatment influences rheological markers and most likely improves metabolism in affected retinal areas, resulting not only in absorption of soft drusen but also reduction or complete disappearance of drusenoid retinal pigment epithelium detachments. However, the character of the treatment process has raised suspicion that there is a decrease not only in cholesterol but also in antioxidants, such as vitamin E and vitamin A.Methods: Twenty-three patients with the progressive dry form of age-related macular degeneration were each treated with 8 procedures of rheohaemapheresis. We measured levels of vitamin E (α-tocopherol), the vitamin E/cholesterol ratio in serum and lipoproteins (VLDL, LDL, HDL). Vitamin E in erythrocyte membrane and serum vitamin A (retinol) were also measured. These parameters were determined before and after rheohaemapheresis. Erythrocyte superoxide dismutase, erythrocyte glutathione peroxidase and serum malondialdehyde were analysed as markers of antioxidant activity and lipid peroxidation, respectively.Results: In serum, the VLDL and LDL fraction ratios of vitamin E/cholesterol increased significantly. Additionally, the HDL fraction ratio showed an increase but this was not statistically significant. The patients showed no clinical signs of vitamin E deficiency, and their serum concentrations of vitamin E did not differ from normal values. The results show that rheohaemapheresis in addition to causing a significant reduction in atherogenic LDL cholesterol, may have favourable additive anti-atherogenic effects due to a relative increase in the content of vitamin E in the lipoprotein fractions.
Keywords: rheohaemapheresis; age related macular degeneration; vitamin E; vitamin E/cholesterol ratio; antioxidants